2019
DOI: 10.1209/0295-5075/125/30007
|View full text |Cite
|
Sign up to set email alerts
|

Geometry of quantum evolution in a nonequilibrium environment

Abstract: We theoretically study the geometric effect of quantum dynamical evolution in the presence of a nonequilibrium noisy environment. We derive the expression of the time dependent geometric phase in terms of the dynamical evolution and the overlap between the time evolved state and initial state. It is shown that the frequency shift induced by the environmental nonequilibrium feature plays a crucial role in the geometric phase and evolution path of the quantum dynamics. The nonequilibrium feature of the environme… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 83 publications
(114 reference statements)
1
10
0
Order By: Relevance
“…in agreement with the expression (115), where the minimum is attained by the amplitudes w(s) fulfilling the parallel transport condition (118). This is the Bures metric.…”
Section: The Bures Metricsupporting
confidence: 81%
“…in agreement with the expression (115), where the minimum is attained by the amplitudes w(s) fulfilling the parallel transport condition (118). This is the Bures metric.…”
Section: The Bures Metricsupporting
confidence: 81%
“…Hence, it is necessary to take into extensive consideration the memory effects of the environment, namely, the non-Markovian statistical properties of the environmental noise, to study the dynamical evolution of the quantum system. Recently, the non-Markovian RTN with an exponentially correlated memory kernel has been discussed [57] and widely used to study the relevant issues of open quantum systems [58][59][60][61][62].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in physical systems, the transient and ultra-fast dynamical processes can happen on sufficiently short periods such that the initial non-equilibrium state induced by system-environment coupling may not have the ability to return to equilibrium [30][31][32][33][34][35][36]. Moreover, in the recent years, it was shown that non-equilibrium feature of environment with non-stationary statistical properties gives rise to frequency shift which has a dominant effect on the reducing of decoherence effects, quantum speed limits and geometric phase of the quantum systems [37][38][39][40]. To the best of our knowledge, phenomena of freezing discord and sudden transition from classical to quantum decoherence in the presence of non-equilibrium environments have not been studied yet.…”
Section: Introductionmentioning
confidence: 99%